The added value of clinical radiopharmacists in nuclear medicine: The example of glomerular filtration rate assessment in kidney donors. (10th June 2020) - Dinet, Juliette; Becker, Stéphanie; Le Cloirec, Joseph; Bohn, Pierre
Abstract: What is known and objectives: In Europe, the pharmaceutical supply of chromium‐51 has been stopped. However, this isotope is necessary for the evaluation of glomerular filtration rates. It is possible to replace it with technetium‐99m, but the validation of this change in the measurement method must be carried out. Methods: A retrospective analysis of chromium‐51 data from January 2018 to January 2019 was performed, followed by a study from January 2019 to January 2020 using the technetium tracer. The patients were different in the both study groups, and none had an eGFR below 50 mL min −1 . A cost analysis was performed. Patient exposure to ionizing radiation was studied for both methods. Results and discussion: Seventy‐eight patients were included in the study. In total, 42 EDTA‐ 51 Cr and 36 DTPA‐ 99m Tc examinations were conducted and compared. There were no significant differences between the methods used to assess renal function ( P = .351). The results of cost analysis and patient radiation exposure were in favour of DTPA‐ 99m Tc examinations. What is new and conclusion: Within the limitations of a retrospective study of two patient cohorts, there was no significant difference between the results obtained with chromium‐51 and technetium‐99m tracers. In addition, with the use of DTPA‐ 99m Tc, operating costs and patient exposure to ionizing radiation were reduced, and clinical activity was maintained for the patients' benefit. Radiopharmacists are able to react quickly to supply contingencies, reduce operating costs and maintain the quality of medical examinations. Abstract : This study deals with the replacement of EDTA‐ 51 Cr by DTPA‐ 99m Tc for the determination of GFR in kidney donors. The results obtained by these two techniques were similar. The economic study was in favour of the DTPA‐ 99m Tc technique.